Α‐Synemin localizes to the M‐band of the sarcomere through interaction with the M10 region of titin. Issue 24 (11th November 2014) - Prudner, Bethany C.; Roy, Pritam Sinha; Damron, Derek S.; Russell, Mary A.
Abstract : α‐Synemin contains a unique 312 amino acid insert near the end of its C‐terminal tail. Therefore we set out to determine if the insert is a site of protein–protein interaction that regulates the sub‐cellular localization of this large isoform of synemin. Yeast‐two hybrid analysis indicated that this region is a binding site for the M10 region of titin. This was confirmed with GST pull‐down assays. Co‐immunoprecipitation of endogenous proteins indicated close association of the two proteins in vivo and immunostaining of cardiomyocytes demonstrated co‐localization of the proteins at the M‐band of the sarcomere. Abstract : The 312 amino acid insert unique to α‐synemin interacts with the M10 domain of titin. Endogenous α‐synemin and titin co‐immunoprecipitate from HL‐1 cells. Endogenous α‐synemin localizes to the M‐band in cardiomyocytes.